SURGICAL OUTCOME OF THREE MUSCLES SURGERY IN ONE SINGLE PROCEDURE OF LARGE-ANGLE EXOTROPIA: A CASE REPORT: Poster Presentation - Case Report - Resident - Jatikusuma, Anas; Prastyani, Reni (Majalah Oftalmologi Indonesia, 2023)
Introduction : The management of large-angle horizontal strabismus poses special difficulties. Literature has outlined large-angle strabismus in a variety of ways. A threshold of 40 to 60 PD has been employed to determine large-angle strabismus. Case Illustration : A 19-year-old male with complaint of right eye that had been crossed outward since he was 12 years old. There was 90 prism diopter exotropia in near, distance, upgaze, and downgaze. The patient underwent bilateral lateral rectus recession of 10 mm and unilateral medial rectus resection of 6.5 mm in the right eye. Post-operative outcome revealed orthophoria without any misalignment of prism diopter examination in 1 day, one week, and two weeks follow-up. Discussion : When the deviation exceeds 50 prism diopter, there is no established consensus regarding the number and quantity of extraocular rectus muscles for surgery. The lack of uniform criteria and suggested surgical dosage is the greatest obstacle in using three muscles surgery. In this case, we used surgical dose according to Kenneth Wright exotropia binocular surgery table. We performed bilateral rectus lateral recession of 10 mm and a right rectus medial resection of 6.5 mm. This surgical dose gives good outcome. Moreover, this option can leave one horizontal rectus muscle unharmed. Conclusion : Determination of the surgical dose is essential in the management of large-angle exotropia. Appropriate surgical dose results in excellent outcomes with low risk of residual deviation.